The follow-up of alumni as a strategic action in Brazilian universities - Correa, Claudia Prim; Martins, Cibele Barsalini; dos Santos, Areli Andreia (International Journal for Innovation Education and Research, 2017)
In Brazilian universities, considered as the complex organization because of its multiple objectives, high specialization and low degree of coordination, the follow-up of alumni presents itself as a strategic action. The purpose of following-up alumni consists in obtaining information that enables evaluating the impact of graduate programs on the professional and academic practice of alumni, as well as enhance the qualification of regular students. Taking these aspects into consideration, in this theoretical work we discuss aspects related to Brazilian universities and the follow-up of alumni as a strategic action in this context.